An assessment of ecological impacts of community-based restoration on communal grasslands in the Drakensberg foothills - Marx, Dane Lee (Department of Biological Sciences, 2015)
Okhombe is a ward in the Northern Drakensberg where community based restoration of degraded lands has been conducted for over a decade. In this important water supply region, payment for ecosystem services has been suggested as a means through which to conserve biodiversity, improve veld condition, provide income to local communities, and ensure water security. However, before such alternative market mechanisms can be considered, the effects of community based restoration must be properly quantified. The primary aim of this study was to determine some of the ecological impacts of community based restoration in these communal grasslands.